2021
DOI: 10.1111/jan.15047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 and other infectious conditions requiring isolation on the provision of and adaptations to fundamental nursing care in hospital in terms of overall patient experience, care quality, functional ability, and treatment outcomes: systematic review

Abstract: Aim This systematic review identifies, appraises and synthesizes the evidence on the provision of fundamental nursing care to hospitalized patients with a highly infectious virus and the effectiveness of adaptations to overcome barriers to care. Design Systematic review. Data Sources In July 2020, we searched Medline, PsycINFO (OvidSP), CINAHL (EBSCOhost), BNI (ProQuest), WHO COVID‐19 Database ( https://search.bvsalud.org/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 110 publications
2
18
0
1
Order By: Relevance
“…These reports mirror findings from our own systematic review on fundamental nursing care in pandemic situations, where we identified wearing personal protective equipment, adequate staffing, infection control procedures and emotional challenges as barriers to care (Whear et al, 2022 ). Our review demonstrated the poor quality of research on pandemic nursing practice with only 19 empirical articles in 64 included papers covering five pandemics.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…These reports mirror findings from our own systematic review on fundamental nursing care in pandemic situations, where we identified wearing personal protective equipment, adequate staffing, infection control procedures and emotional challenges as barriers to care (Whear et al, 2022 ). Our review demonstrated the poor quality of research on pandemic nursing practice with only 19 empirical articles in 64 included papers covering five pandemics.…”
Section: Introductionsupporting
confidence: 74%
“…Our results make a substantial contribution to the disappointingly scant existing empirical literature on fundamental nursing care in a pandemic, reviewed in (Whear et al, 2022 ). Of the 12 previous qualitative studies in this area, most are very small and report nurses’ experiences of care, not their adaptive strategies.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations